2023
DOI: 10.1002/adfm.202212640
|View full text |Cite
|
Sign up to set email alerts
|

Triplet Excitons and Associated Efficiency‐Limiting Pathways in Organic Solar Cell Blends Based on (Non‐) Halogenated PBDB‐T and Y‐Series

Abstract: The great progress in organic photovoltaics (OPV) over the past few years has been largely achieved by the development of non‐fullerene acceptors (NFAs), with power conversion efficiencies now approaching 20%. To further improve device performance, loss mechanisms must be identified and minimized. Triplet states are known to adversely affect device performance, since they can form energetically trapped excitons on low‐lying states that are responsible for non‐radiative losses or even device degradation. Haloge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 87 publications
0
8
0
Order By: Relevance
“…S4,† the ground state bleaching (GSB) peaks of neat PM6 films are centered at ∼620 nm, which correspond well with the steady absorption spectra of the corresponding neat films. 44 The PY-IT presents a relatively broad GSB signal with characteristic peaks at ∼710 nm and ∼800 nm. The TA spectra of the PM6/PY-IT and PM6/PY-IT:L8-BO films at different probe delay times are displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…S4,† the ground state bleaching (GSB) peaks of neat PM6 films are centered at ∼620 nm, which correspond well with the steady absorption spectra of the corresponding neat films. 44 The PY-IT presents a relatively broad GSB signal with characteristic peaks at ∼710 nm and ∼800 nm. The TA spectra of the PM6/PY-IT and PM6/PY-IT:L8-BO films at different probe delay times are displayed in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[15] The electron mobility of long oligomers also meets the requirements of OPD devices (Figure S27). We use OTB4 as the electron acceptor and select commercially available Poly [(2,6-(4,8-bis(5-(2-ethylhexyl) thiophen-2-yl)-benzo-[1,2-b:4,5-b']dithiophene))-alt- (5,5-(1',3'-di-2thienyl-5',7'-bis(2-ethylhexyl)benzo[1', 2'-c:4',5'c']dithiophene-4,8-dione))] (PBDB-T, see Figure 5b) [16] as the electron donor to construct the OPDs. The device structure is ITO/ZnO/PBDBÀ T: OTB4/MoO 3 /Ag (Figure 5a).…”
Section: Methodsmentioning
confidence: 99%
“…It has been widely reported that more crystalline phases have increased triplet exciton diffusion lengths and mobilities, and so we propose that the enhanced long-range OOP ordering in PM6:Y11 increases the rate constant of TTA in this blend relative to that in PM6:Y6. [30][31][32][33]68]…”
Section: Grazing-incidence Wide-angle X-ray Scattering (Giwaxs)mentioning
confidence: 99%